Justice - Hegtvedt, Karen A.; Clay-Warner, Jody, 1968- (Advances in group processes ;, 2008)
Justice processes operate in small groups, organizations, institutions, as well as society as a whole. Scholars from a variety of disciplines tackle a wide range of fundamental issues about justice. This volume brings together sociologists and psychologists who address issues pertaining to distributive, procedural, and interactional justice using a range of methodologies. Substantively, authors grapple with issues relevant to the processes underlying justice evaluations, including motivations, perceptions, identities, ideologies and exclusionary practices. They also consider the consequences of these evaluations, focusing on negative emotions, moral outrage, social action, and dispute resolution choices.In doing so, this volume highlights the role of the social structure in justice processes, thereby emphasizing that justice is more than just threads of individual assessments. Instead, justice is a collective process through which groups construct meaning and maintain the fabric of society.